1981
DOI: 10.1139/b81-207
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to arsenate toxicity in the blue-green alga Synechococcus leopoliensis

Abstract: Phosphate-limited growth of the blue-green alga Synechococcus leopoliensis was unaffected by arsenate at up to 200 μM. Phosphate uptake, during growth and also under nongrowing conditions, was not measurably affected by arsenate even at 50 × the phosphate concentration. Arsenate uptake was very low and was not influenced by light or by external phosphate. It is concluded that phosphate transport in Synechococcus is highly phosphate specific. The ecological aspects of this specificity are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…variabilis was very resistant to the toxic effects of arsenate, as are other cyanobacteria (6,21). Concentrations of arsenate in the 10 to 100 mM range had a toxic effect, but at the lower arsenate concentrations, only cells previously starved for phosphate and then grown with arsenate in the absence of phosphate were particularly sensitive.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…variabilis was very resistant to the toxic effects of arsenate, as are other cyanobacteria (6,21). Concentrations of arsenate in the 10 to 100 mM range had a toxic effect, but at the lower arsenate concentrations, only cells previously starved for phosphate and then grown with arsenate in the absence of phosphate were particularly sensitive.…”
Section: Resultsmentioning
confidence: 94%
“…Others have reported that arsenate did not compete with phosphate for transport into Synechococcus spp. However, they did not try concentrations of arsenate higher than 100 or 200 ,uM (6,11). Arsenate did inhibit transport of phosphate into A. variabilis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some microalgae and cyanobacteria, including Chlorella (Maeda et al 1985) and Synechococcus (Budd and Craig 1981), show some resistance to arsenic. Some macroalgae are known to concentrate arsenic to far higher levels than in the surrounding water (Kaise et al 1988).…”
Section: Introductionmentioning
confidence: 99%